Spectral index of the Galactic foreground emission in the 50–87 MHz range. Issue 2 (17th May 2021) - Spinelli, M; Bernardi, G; Garsden, H; Greenhill, L J; Fialkov, A; Dowell, J; Price, D C
ABSTRACT: Total-power radiometry with individual meter-wave antennas is a potentially effective way to study the Cosmic Dawn ( z ∼ 20) through measurement of the sky brightness arising from the 21 cm transition of neutral hydrogen, provided this can be disentangled from much stronger Galactic and extra-galactic foregrounds. In the process, measured spectra of integrated sky brightness temperature can be used to quantify the foreground emission properties. In this work, we analyse a subset of data from the Large-aperture Experiment to Detect the Dark Age (LEDA) in the 50–87 MHz range and constrain the foreground spectral index β in the northern sky visible from mid-latitudes. We focus on two zenith-directed LEDA radiometers and study how estimates of β vary with local sidereal time (LST). We correct for the effect of gain pattern chromaticity and compare estimated absolute temperatures with simulations. We select a reference data set consisting of 14 d of observations in optimal conditions. Using this data set, we find, for one radiometer, that β varies from −2.55 at LST <6 h to a steeper −2.58 at LST ∼13 h, consistently with sky models and previous southern sky measurements. In the 13 − 24 h LST range, however, we find that β varies between −2.55 and −2.61 (data scatter ∼0.01). We observe a similar β versus LST trend for the second radiometer, although with slightly smaller | β | over the 24 h, in the −2.46 < β < −2.43 range (data scatter ∼ 0.02). Combining all data gathered during the extended campaign between mid-2018 and mid-2019, and focusing on the LST = 9−12.5 h range, we infer good instrument stability and find −2.56 < β < −2.50 with 0.09 < Δ β < 0.12.